Clinic follow-up of orthopaedic trauma patients during and after the post-surgical global period: a retrospective cohort study - Abhiram R. Bhashyam; Sravya T. Challa; Hannah Thomas; Edward K. Rodriguez; Michael J. Weaver (BMC Musculoskeletal Disorders, 2023)
Abstract Background Insurance status is important as medical expenses may decrease the likelihood of follow-up after musculoskeletal trauma, especially for low-income populations. However, it is unknown what insurance factors are associated with follow-up care. In this study, we assessed the association between insurance plan benefits, the end of the post-surgical global period, and follow-up after musculoskeletal injury. Methods This is a retrospective cohort study of 394 patients with isolated extremity fractures who were treated at three level-I trauma centers over four months in 2018. Paired t-tests were utilized to assess the likelihood of follow-up in relation to the 90-day post-surgical global period. Regression analysis was used to assess factors associated with the likelihood of follow-up. Supervised machine learning algorithms were used to develop predictive models of follow-up after the post-surgical global period. Results Our final analysis included 328 patients. Likelihood of follow-up did not significantly change while within the post-surgical global period. When comparing follow-up within and outside of the post-surgical global period, there was a 20.1% decrease in follow-up between the 6-weeks and 6-month time points (68.3% versus 48.2%, respectively; p < 0.0001). Medicaid insurance compared to Medicare (OR 0.27, 95% confidence interval (CI) = [0.09, 0.84], p = 0.02) was a predictor of decreased likelihood of follow-up at 6-months post-operatively. Conclusions Our study demonstrates a statistically significant decrease in follow-up for orthopaedic trauma patients after the post-surgical global period, particularly for patients with Medicaid or Private insurance.